High-risk pollutants in wastewater - Ren, Hongqiang; Zhang, Xuxiang (Elsevier, 2020)
High-Risk Pollutants in Wastewater presents the basic knowledge regarding the diversity, concentrations, and health and environmental impacts of HRPs in municipal wastewater. The book summarizes information on the types (e.g. heavy metals, toxic organics and pathogens) and toxicities of HRPs in wastewater. In addition, it describes ecological and health hazards arising from the living things' direct/indirect contacts with the HRPs during their full lifecycles (generation, disposal, discharge and reuse) in wastewater or water environments. Sections cover the concepts of appropriate technology for HRP hazard/risk assessment and wastewater treatment/reuse and the issues of strategy and policy for increasing risk control coverage. Finally, the book focuses on the resolution of water quality monitoring, wastewater treatment and disposal problems in both developed and developing countries. --